Fostering creativity and self-efficacy through collaborative learning using generative Artificial Intelligence (AI) in product design visualization process - Muhammad Jameel, Mohamed Kamil; Amirul Fahmi, Razali; Rosalam, Che Me; Mohd Najib, Abdullah Sani (Aalborg University Open Publishing, 2025)
Generative models in Artificial Intelligence (AI) are increasingly employed across diverse fields, including product design, for tasks like shape recognition and design creation. This trend underscores generative models' ability to bridge offline and online environments in creative endeavors. The article investigates the potential of integrating generative image AI into visualization process among product design students. Using image-based research analysis and semi-structured interviews, this study involved 50 product design students as respondents. The findings highlight that integrating generative AI tools, particularly the ChatGPT 4.0, significantly improves students' creativity and self-efficacy through collaborative learning, and streamlines the design process. The findings also close the gap between creative concepts and practical applications, and offers a robust framework for evaluating AI-generated content. The contribution of the study underscores the transformative potential of generative AI tools in product design education, showcasing the effectiveness in fostering creativity, efficiency, and design quality through collaborative learning.